Kapasitas Organisasi dalam Penyelenggaraan Kearsipan di Dinas Perpustakaan dan Kearsipan Kota Bandar Lampung - Ristanti Simanjuntak; Simon Sumanjoyo Hutagalung; Vina Karmilasari (Jurnal Administrativa, 2021)
Archives in administrative activities have a very important role, one of its functions is as the center of the nation's memory and evidence of legal accountability. However, the implementation of archiving in Indonesia, especially local governments, is currently still less than optimal. In 2017, the organization of archiving in Indonesia received the predicate of 93% in bad condition, for this reason, adequate organizational capacity is needed. Organizational capacity is the ability that an organization has that is useful for solving problems and can achieve the goals set. This research was conducted at the Department of Library and Archives of Bandar Lampung City with the aim of identifying and analyzing these offices in organizing archives. The method used in this research is descriptive qualitative with data analysis techniques derived from observation, documentation and in-depth interviews. The results of this study are described based on the components of organizational capacity consisting of human resources, infrastructure, technology, financial resources, leadership strategies, program and process management, cooperation and relationships with other parties. Organizing the archives of the Bandar Lampung City Library and Archives Service has been carried out since 2008. However, archiving has not been carried out optimally because the capacity of the office is inadequate.